Asymptotic methods on the solution of diffraction problems on the convex impedance cylinders - Vyunnik, V. I.; Zvyagintsev, A. A. (Видавництво Національного університету "Львівська політехніка", 2009)
In work are considered problems of diffraction of electromagnetic waves by the impedance convex cylinder for two cases : the observation point and source point are located on removal from the cylinder and a source point is located in the close vicinity of the convex cilinder. Process of obtaining asymptotic interpolation formulas, suitable for calculations both in shadow and in lighted zones is described.
Keywords: diffraction; asymptotic method; interpolation